Design and Implementation of Schoology-Based Blended Learning Media for Basic Physics I Course (Jurnal Pendidikan IPA Indonesia, 2017)
This research was conducted to: (1) design a Schoology-based blended learning media for Basic Physics I course on the topics of vector quantity, linear motion, and translational dynamics, (2) describe the validity of the product, (3) describe the product’s effectiveness in enhancing students’ conceptual understanding and problem solving skills, and (4) describe students’ responses towards the media and blended learning model. The development procedures employed were ADDIE model which consisedt of five stages: analysis, design, development, implementation, and evaluation. In development stage, the assessment had been conducted by two experts to assess validity of media both in content and construct aspects. The results showed that the validities in content aspect and construct aspect were “very good” and “good”, respectively. The results from classroom implementation revealed the effectiveness of the product in enhancing students’ conceptual understanding and problem solving skills. Students’ responses towards the product’s utility, attractiveness, and easiness as blended learning media were also positive. The conclusion was that the media was valid and effective as blended learning media of Basic Physics I course.